Enseigner les humanités numériques en Tunisie : conditions, pratiques et choix - Delphine Cavallo; Aïda Chebbi (Humanités Numériques)
The teaching of the digital humanities in Tunisian universities, though present, is not well structured, and it has not yet been the subject of research or didactic analysis. This article reflects on diverse experiences of the authors to explore the way in which these courses are used in a national academic space that is embedded within international exchanges but possesses specific characteristics. In the light of the existing literature on the subject, the aim is to highlight the adaptations of pedagogical practices in the digital humanities to the Tunisian situation. Our focus is on the feasibility of such teaching in Tunisia, at least to Tunisian students, showing how our experiences have influenced our thinking in designing an online introductory digital humanities course as part of the Erasmus + project Raqmyat. We conclude that the analysis of pedagogical practices in real-life situations must be part of the ethics of teaching digital humanities.